Clinico‐immunological outcomes of HCV‐cured cryoglobulinemia: Lower relapse rate with interferon‐based than interferon‐free therapy. (29th December 2020) - Colantuono, Stefania; Marrapodi, Ramona; Del Padre, Martina; Collalti, Giulia; Garzi, Giulia; De Santis, Adriano; Fiorilli, Massimo; Basili, Stefania; Visentini, Marcella; Casato, Milvia
Abstract: Sustained virological response (SVR) obtained with interferon (IFN) or with direct‐acting antivirals (DAAs) is commonly followed by response of hepatitis C virus (HCV)‐associated mixed cryoglobulinemia vasculitis (MCV), but relapse of MCV despite SVR has been reported in several patients after DAAs and rarely after IFN. Since relapses could have been overlooked in studies with IFN, we retrospectively compared the outcomes of MCV in SVR patients treated with DAAs (n = 70) or IFN (n = 39) followed‐up, respectively, for 30.5 (range 11‐51) or 48 months. Groups were comparable for demographics and clinics and response rates of MCV were similar (92% and 86%); however, DAA‐treated patients less efficiently reduced cryoglobulins ( P = .006) and circulating B‐cell clones ( P = .004), and had more frequently relapses of MCV (18% vs 3%, P = .028) and need for rituximab therapy ( P = .01). Although largely inferior on an intention‐to‐treat basis, IFN may be superior to DAAs on clinico‐immunological outcomes possibly owing to its antiproliferative activity.